Perbandingan Arah Serat Material Komposit Natural Fiber Reinforced Polymer (NFRP) Serat Nenas Untuk Perkuatan Struktur Beton - Salsabila, Shafira; Muhammad Riswandy; Febrina Dian Kurniasari; Tjut Rizqi Maysyarah Hadi (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2025)
Concrete structures that experience performance degradation require repair and strengthening to maintain their load-bearing capacity. One method that has gained attention is the use of composite materials, specifically Natural Fiber Reinforced Polymer (NFRP), which consists of adhesives reinforced with natural fibers. Pineapple fiber is a promising natural fiber for NFRP due to its abundance, low production cost, environmental friendliness, and high tensile strength. This study aims to investigate the adhesion behavior between NFRP composite materials and concrete, as well as to observe the failure modes of both concrete and NFRP under tensile loading. Concrete specimens measuring (100 x 100 x 300) mm were reinforced with pineapple fiber NFRP of (50 x 240) mm, with fiber orientations arranged in both unidirectional and random patterns. The results showed that the maximum tensile strength of the random pineapple fiber NFRP reached 31.59 MPa. The highest load capacity recorded was 4360 kg, observed in the LP3-SNS-C test specimen. The failure mode occurred as a fracture of the pineapple fiber NFRP in the center of the specimen’s cross-section on both sides.